Rater goals as a function of appraisal purpose and ratee performance level - Kerst, Melinda E., author; Cleveland, Jeanette, advisor; Bell, Paul A., committee member; Pegnetter, Richard, committee member; Thornton, George C., 1940-, committee member (Colorado State University. Libraries, 1994)
The goals raters have in mind when evaluating employee performance has not been a central area of focus in traditional performance appraisal literature (Cleveland & Murphy, 1992; Murphy and Cleveland , 1991). The purpose of the current study was to empirically examine rater goals and how they vary as a function of appraisal purpose (administrative or developmental) and ratee performance level (poor, average, or outstanding). The method used in this study was based upon procedures used in the creation of behaviorally anchored rating scales. The study was divided into three main phases: phase one involved goal generation, phase two involved retranslation of goals, and phase three involved rating the importance of goals. Analysis of variance and t-tests were conducted to examine the degree to which goals differed in rated importance based upon appraisal purpose ( developmental or administrative) and ratee performance level (poor, average, outstanding). Results supported the influence of appraisal purpose and ratee performance level on rated goal importance. In addition, evidence supporting an interaction of purpose and performance level on rated goal importance was found. Interpretations, limitations, and implications for organizations and future research are discussed.
Keywords: Employees -- Rating of; Performance standards